70 nm, broadly tunable passively Q-switched thulium-doped fiber laser with few-layer Mo0.8W0.2S2 saturable absorber - Ahmad, H.; Samion, M.Z.; Sharbirin, A.S.; Ismail, M.F.; Zulkifli, Mohd Zamani; Thambiratnam, K. (2018)
In this work, a thin Mo0.8W0.2S2 film is proposed and fabricated for the use as a saturable absorber (SA) in a thulium-doped fiber laser (TDFL) cavity. The few-layer Mo0.8W0.2S2 nanoparticles are obtained through hydrothermal exfoliation as a thin film and suspended in a polymer host, which is then placed between two fiber ferrules to serve as an SA. The proposed laser is capable of generating outputs with a maximum repetition rate of 65.79 kHz and a minimum pulse width of 1.84 µs at the maximum pump power of 168.92 mW, as well as pulse energies andpeak powers as high as 35.73 nJ and 13.92 mW. The laser also has a broad tuning output from 1927.2 nm to 1996.8 nm, giving a tuning band of about 70 nm. The generated pulses are stable with a signal-tonoise ratio of 50.0 dB. The proposed laser has a high potential for operation near the 2000 nm wavelength region, with multiple bio-medical and sensing applications.